Statutory Reform Of Administrative Law: The Canadian Experience - MacKinnon, Victor S (Journal of Malaysian and Comparative Law, 2019)
The preamble to the Canadian Constitution expresses Canada’s desire to have a constitution "similr in principle to that of the United Kingdom".